K. ZHENG ET AL.Gold-nanoparticle-based multistage drug delivery system for antitumor therapy. (31st December 2022) - Zheng, Kaikai; Zhou, Dong; Wu, Lili; Li, Jian; Zhao, Bing; Zhang, Shihao; He, Ruiying; Xiao, Lan; Zoya, Iqbal; Yu, Li; Zhang, Yuhong; Li, Yulin; et al.
Abstract: Nanoparticles can promote the accumulation of drugs in tumors. However, they find limited clinical applications because they cannot easily penetrate the stroma of cancer tissues, and it is difficult to control drug release. We developed a multiresponse multistage drug-delivery nanogel with improved tumor permeability and responsiveness to the tumor microenvironment for the controlled delivery of anticancer agents. For this purpose, ∼100 nm multistage drug delivery nanogels with pH, redox, near-infrared stimulation, and enzyme responsiveness were grown in situ using 20 nm gold nanoparticles (AuNPs) via an emulsion-aiding crosslinking technique with cysteine crosslinker. An alginate cysteine AuNP (ACA) nanocarrier can efficiently load the cationic drug doxorubicin (DOX) to produce a multistage drug delivery nanocarrier (DOX@ACA). DOX@ACA can maintain the slow release of DOX and reduce its toxicity. In cancer tissues, the high pH and reductase microenvironment combined with the in vitro delivery of alginate and near-infrared light drove drug release. The developed nanoparticles effectively inhibited cancer cells, and in vivo evaluations showed that they effectively enhanced antitumor activity while having negligible in vivo toxicity to major organs.